2014
DOI: 10.1007/s11738-014-1692-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Festuca rubra L. germination and seedling growth by seed treatment with pathogenic Agrobacterium rhizogenes

Abstract: The study concerned effects of two methods of red fescue seeds treating with wild type Agrobacterium rhizogenes strains (15834 and LBA 1334): soaking and matriconditioning with Micro-Cel E solid carrier. The effects were assessed from germination and seedlings growth rates. The bacterial indole-3-acetic acid (IAA) production and ACC deaminase activity were also determined. Both strains are able to produce the IAA and showed ACC deaminase activity in various amounts. The strains accelerated seeds germination, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The robust growth of roots improves plant fitness due to enhanced water and nutrient uptake through the root from an early growth stage. These growth-promoting effects have also been reported in other studies [ 27 , 35 , 36 ]. Blinskov et al (2014) also emphasized the importance of rapid growth in some areas of high latitude where the arable period is short, representing the effect of Klebsiella planticola TSKhA-91 strain, which induced rapid germination and growth of cucumber seedling under cold stress [ 17 ].…”
Section: Discussionsupporting
confidence: 87%
“…The robust growth of roots improves plant fitness due to enhanced water and nutrient uptake through the root from an early growth stage. These growth-promoting effects have also been reported in other studies [ 27 , 35 , 36 ]. Blinskov et al (2014) also emphasized the importance of rapid growth in some areas of high latitude where the arable period is short, representing the effect of Klebsiella planticola TSKhA-91 strain, which induced rapid germination and growth of cucumber seedling under cold stress [ 17 ].…”
Section: Discussionsupporting
confidence: 87%
“…In general, the highest M. truncatula seedling growth promotion was obtained after inoculation with strains which produced most of the IAA (between 30 and 47 µg ml −1 ), with simultaneous absence or very low activity of ACCD. Previously, we also suggested that IAA production rather than ACCD activity in two Agrobacterium rhizogenes strains, 15834 and LBA1334, might be responsible for the stimulation of the grass Festuca rubra L. seed germination, seedling emergence and development upon seed inoculation; mainly by increasing growth of lateral roots and more complex architecture of the branching root system (Król et al 2014 ). We compared the effects of seed inoculation of the two strains tested with the ability to produce IAA and of exogenous application of IAA at concentrations corresponding to IAA production by these strains.…”
Section: Discussionmentioning
confidence: 94%
“…A poor seedling emergence leads to a poor turfgrass stand, and weed infestations (Shiade & Boelt, 2020) results waste of time and resources. It is very important, particularly under sub-optimal conditions, to reduce the period between sowing and seedling emergence in turfgrass (Krol et al, 2014).…”
Section: Introductionmentioning
confidence: 99%